Evaluation of CBC Parameters in Relation to PCR Test Results in Diagnosing Pediatric COVID-19 Disease - Bagci, Zafer; Ugur, Ayşe Ruveyda; Ugur, Cüneyt (Journal of Pediatric Infectious Diseases, 2021)
Objective This study aimed to investigate whether complete blood count parameters have predictive properties in diagnosing coronavirus disease 2019 (COVID-19) in regard to positive polymerase chain reaction (PCR) test in children with a prediagnosis of COVID-19, and whether these parameters are related to the severity of clinical findings in children with COVID-19.Methods This retrospective cross-sectional study included children who were hospitalized with a possible diagnosis of COVID-19 and had undergone PCR testing in the COVID-19 children's clinic. Probable case definition was made according to the COVID-19 diagnostic and therapeutic guidelines of the Ministry of Health of the Republic of Turkey.Results A total of 133 patients were included in the study, of which 46 (34.6%) were negative for the PCR test and 87 (65.4%) were positive for the PCR test. white blood cell (WBC), neutrophil, lymphocyte, and platelet levels were significantly lower in the PCR positive group than in the PCR negative group. The platelet to mean platelet volume ratio (PLT/MPV) was significantly lower in the PCR positive group than the PCR negative group, whereas the platelet distribution width (PDW) of the PCR positive patient group was significantly higher than the PCR negative group. For the multivariable model with PDW and neutrophil to lymphocyte ratio/age factors included, F1 score was 0.864, area under the receiver operating characteristics was 0.804, and area under the precision-recall curve was 0.873. The decision tree had a 72.9% cross-validation accuracy value.Conclusion WBC, neutrophils, lymphocytes, platelets, PLT/MPV, and PDW parameters could be used in conjunction with clinical symptoms and findings to predict the PCR test result.
Keywords: COVID-19; complete blood count; polymerase chain; platelet to mean platelet volume ratio; platelet distribution width